FROM TOUCH TO TRUST: THE ROLE OF EMOTIONAL ENGAGEMENT AND BRAND TRUST IN DRIVING IMPULSIVE BUYING OF SCIENTIFIC PRODUCTS DURING TIKTOK LIVE STREAMING - Diah Sulistia; Muhammad Dharma Tuah Putra; Husni Muharram Ritonga (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
Study This aim explore Factors that influence impulsive buying behavior Students on TikTok Live Streaming Commerce products Skintific with use Stimulus–Organism–Response (SOR) framework . In this model , Interactivity is positioned as the main stimulus , while Affective Engagement and Brand Trust play a role as a mediating organism the influence of stimulus on response in the form of behavior purchase impulsive approach​ quantitative used through Structural Equation Modeling (SEM-PLS) method with involving 300 respondents active students of Panca Budi Development University Medan watch TikTok Live Streaming and have experience shop product beauty online . Research results show that interactivity has an effect significant on affective engagement and brand trust, as well as in a way direct and indirect direct trigger impulsive buying behavior . Findings This confirm that combination real-time interaction , engagement emotional , and trust towards the brand playing role important in push decision purchase spontaneously in the Live Streaming Commerce ecosystem . In theoretical , research This enrich literature about behavior digital consumers , while in a way practical give implications for beauty brands For optimizing communication strategies interactive in increase effectiveness marketing via TikTok Live Streaming.